Mobile Advertising: Behavioural Intention Among Undergraduates in Malaysia - Sook Fern, Yeo; Cheng Ling, Tan; Kah Boon, Lim; Wee Lian Fong, Stany; Ming Jie, Fong (International Journal of Engineering and Technology, 2018)
In today's world, smartphone has become a necessity in our daily life. All the businesses will take advantage of mobile phone to advertise their product to create awareness. Due to the new techniques and technologies, mobile advertising has become more efficiently (Saadeghvaziri & Hosseini, 2011). Therefore, we conduct the factors that influence the effects of mobile advertising campaign, especially the case of Short Messaging Service (SMS). According to Yeo, Tan and Lim (2016), mobile technology is growing intensively. Smartphone become more convenience and able to let users to have fun while they experience mobile device shopping, and they able to open many browsers so they can either comparing the price, shopping or purchasing good. The research framework such as the five independent variables (perceived usefulness, perceived ease of use, irritation, credibility, and informativeness) has connected with dependent variable (behavioural intention). This research design has planned to involve 300 respondents. The unit analysis for this study is all undergraduates in Malaysia. A total of 274 undergraduates have participated in this study which comprised of 91% of the response rate. There are about 21.5% experiencing the mobile advertising through SMS/MMS. Furthermore, the frequency of the respondent towards these mobile advertisement is approximately 24.5%. The findings revealed that four direct relationships hypothesized namely perceived usefulness, perceived ease of use, credibility and informativeness were significantly related to the behavioural intention towards mobile advertising.Â Â